Correlation of miRNA-21 and blood Cr levels with tumor infiltration and distant metastasis in renal cancer patients: miRNA-21 and metastasis in renal cancer patients - Li, Hualei; Qu, Lili (Cellular and Molecular Biology, 2022)
The object of this study was to explore the correlation analysis between miRNA-21 and blood Cr levels with tumor invasion and distant metastasis in renal cancer patients. For this purpose 49 cases of renal cancer patients treated in our hospital from February 2018 to March 2020 were selected as the study group, and another 165 cases of renal benign tumors that were pathologically confirmed in our hospital during the same period were selected as the control group. MiRNA-21 and blood Cr levels, miRNA-21 and blood Cr levels at different stages, and miRNA-21 and blood Cr levels when tumor invasion and distant metastasis were present were compared between the two groups. Results showed that compared with the control group, the levels of miRNA-21 and blood Cr in the study group increased, the difference was significant (P < 0. 05); compared with stage I patients, the levels of miRNA-21 and blood Cr in stage II patients increased, compared with stage II patients, the levels of miRNA-21 and blood Cr in stage III patients increased, compared with stage III patients, the levels of miRNA-21 and blood Cr in stage IV patients increased, the difference was significant Compared with the case without tumor invasion, the levels of miRNA-21 and blood Cr in the case of tumor invasion were increased, the difference was statistically significant (P < 0. 05); compared with the case without distant metastasis, the levels of miRNA-21 and blood Cr in the case of tumor distant metastasis were increased, the difference was significant (P < 0. 05) When distant metastasis, miRNA-21 and blood Cr levels increased significantly, which showed that miRNA-21 and blood Cr levels were positively correlated with tumor invasion and distant metastasis; compared with the control group, TIMP1, TIMP2, MACC1 protein expression in the study group increased, and the three showed a positive correlation, the difference was significant (P < 0. 05). It is concluded when renal cancer patients were tested, we found that miRNA-21 and blood Cr levels were abnormally increased, and the two had a certain correlation with renal cancer tumor invasion and distant metastasis, which showed a positive correlation.